Evaluation of the Cardiovascular Diseases Prevention Program on changing health behaviors implemented in the local community of Ropczyce and Sędziszów district in Poland - Kosydar-Bochenek, Justyna; Malinowska-Cieślik, Marta; Lewandowski, Bogumił; Ozga, Dorota; Woźniak, Krystyna (European Journal of Clinical and Experimental Medicine, 2013)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction: Cardiovascular diseases are the main causes of death in Poland and Europe. They are caused as a result of a variety of risk factors, including lifestyle, which from the point of view of prevention, is an important modifiable factor. Effective prevention programs should not only be aimed at early identification of individuals at increased risk of cardiovascular disease. The actions taken within the framework of these programs should be aimed at the promotion of healthy lifestyles related to education on changing health behaviors. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim of study: The aim of this study was to evaluate the effectiveness of the Cardiovascular Diseases Prevention Program implemented on the local level, in the scope of changing health behaviors among program participants. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Method: The study was conducted in 2010 and 2011 in Ropczyce district town in the province of Podkarpackie. The Transtheoretical Model (TTM) was applied to evaluate the results of health education implemented in the program. One year after the intervention, a survey study was conducted by the questionnaire. The following behaviors were analyzed: smoking, low-fat diet, physical activity, regular monitoring of blood pressure, glucose, cholesterol and its fractions in the blood tests and control of the body weight. The study group was consisted of the 104 randomly selected participants of the program residents of the Ropczyce and Sedziszów districts , the ages of 35 to 55 years (mean age 44),. To evaluate the effectiveness of the program the model of “Pretest-Post-Test Only” (Before and After the Program) was applied. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: The results showed significant changes in the prevalence of recommended health behaviors among participants in the program. The following health behaviors have been changed significantly: smoking, the use of low-fat diet, physical activity, regular monitoring of blood pressure, glucose, cholesterol and its fractions in blood tests and the body weight. It was also observed significant differences in the prevalence of recommended behaviors due to selected socio - economic characteristics such as: gender, age, level of education. Women were more likely than men to adhere to recommendations for smoking cessation and dietary change. The youngest and the oldest participants of the programme have complied with the recommendations of weight control more often than other age groups respondents. People with low level of education have changed all of the recommended behaviors, except smoking cessation, more likely than those with higher level of education. <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: It has been shown that participation in this prevention program was associated with a change in health behaviors among a large part of the participants. The change of these behaviors was different due to: age, gender and level of education of the respondents. The success and sustainability of this type of intervention focused on changing behaviors related to prevention of cardiovascular disease conducted on the level of local primary health care depends on the one hand, on professional training in patient’s education, which should use individually tailored educational methods and materials. On the other hand, effective program should consist a long-term implementation of repeated interventions and systematic monitoring and evaluation of its actions.